Presentation on Delphi Approach in research methodology class - Ayob, Mohd Fairullazi (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2014)
The name ‘Delphi’ originates from the Greek Oracle’s skills of interpretation and foresight. This technique was developed by Norman Dalkey of the RAND Corporation in the 1950’s to generate data from a consensus of expert opinion for a U.S. Air Force sponsored military project. It has been used widely in many areas of decision making process particularly to solve complicated problems (e.g. lack of current and reliable data, insufficient theory, data is affluent and profound), and generate forecasts about the future. It is classified as a structured group communication process that involves the process of acquiring responses and exchanging ideas from a group of experts through a number of sequential questionnaires, followed by a synthesis and analysis of opinions and ideas to generate reliable data for the research. It is conducted through rounds of questionnaires where the questionnaires are distributed to the group respondents through electronic devices (i.e. fax, e-mail, website) and the respondents are required to return the completed questionnaires before a specified timeline.